2019
DOI: 10.1002/bem.22171
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression changes reflecting pleiotropic effects of Irpex lacteus induced by low‐­intensity electromagnetic field

Abstract: A polysaccharide of Irpex lacteus, a white‐rot fungus with lignocellulose‐degrading activities, has been used as a commercial medicine for nephritis treatment. Previously, a low‐intensity electromagnetic field (LI‐EMF) was found to increase the biomass and polysaccharide content of Irpex lacteus and induce twists on the cell surface. In this study, RNA‐sequencing (RNA‐seq) technology was used to analyze the underlying mechanism of LI‐EMF's influence on Irpex lacteus. We identified 3268, 1377, and 941 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Fifth, the concentration dependences of the DNA yield are almost identical for magnetic and nonmagnetic ions (Figs. [1][2][3][4][5]; it supports the idea that after switching on radical pair mechanism the subsequent ions, which enter in enzymatic site, are seemingly sitting on the pyrophosphate residue and do not interfere in the radical pair mechanism.…”
Section: Summarizing Comments On the Dna Synthesissupporting
confidence: 66%
See 1 more Smart Citation
“…Fifth, the concentration dependences of the DNA yield are almost identical for magnetic and nonmagnetic ions (Figs. [1][2][3][4][5]; it supports the idea that after switching on radical pair mechanism the subsequent ions, which enter in enzymatic site, are seemingly sitting on the pyrophosphate residue and do not interfere in the radical pair mechanism.…”
Section: Summarizing Comments On the Dna Synthesissupporting
confidence: 66%
“…The exposure of the rats to long-term radiofrequency radiation at 900, 1800, and 2100 MHz results to the oxidative DNA damage and single-strand DNA breaks in the frontal lobe of brain tissues [4]. In a white-rot fungus Irpex lacteus used in medicine and subjected to the electromagnetic treatment there were identified by RNA-and realtime PCR sequencing technologies 3268, 1377, and 941 differentially expressed genes [5]; it was concluded that the global gene expression changes induced by electromagnetic treatment explained the pleiotropic medical effects of Irpex lacteus. It was pointed out that a large number of studies have shown that microwave radiation can cause a series of adverse reactions in the central nervous system, including sleep disorders in addition to learning and memory impairments [6].…”
Section: Electromagnetic Control Of Genesmentioning
confidence: 99%
“…The Control (DMSO treated) and Test (HK treated) samples were harvested after incubation for 36 h. The total RNA was prepared using the Fungal Total RNA198 Isolation Kit (B518629, Sangon Biotech, Shanghai, China), and reverse transcribed with HiScript III RT SuperMix (Vazyme, Nanjing, China) according to the manufacturer’s instructions. The PCR method was based on previous studies ( Sun et al, 2019 ). Primers used for the qRT-PCR are listed in Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…RNA samples were reverse transcribed using HiScript III RT SuperMix (Vazyme, Nanjing, China) to produce cDNA template. The PCR method was based on previous studies (61). The primer details are listed in S3 Table.…”
Section: Qrt-pcr On Corneamentioning
confidence: 99%
“…The total RNA was prepared using the Fungal Total RNA Isolation Kit (B518629, Sangon Biotech, Shanghai, China), and reverse transcribed with HiScript III RT SuperMix (Vazyme, Nanjing, China) according to the manufacturer's instructions. The PCR method was based on previous studies (61). Primers used for the qRT-PCR are listed in S1 Table.…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr) V...mentioning
confidence: 99%